1980
DOI: 10.1093/nar/8.15.3307
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the putative recognition site for coat protein in the RN As of alfalfa mosaic virus and tobacco streak virus

Abstract: The sequence of the 3'-terminal 180 and 140 nucleotides of RNAs 2 and 3, respectively, of tobacco streak virus (TSV) was deduced by reverse transcription in the presence of a specific primer and chain terminators. Homology between the two RNAs was found to be restricted to a 3-terminal region of about 45 nucleotides. The data were compared with the sequence of the homologous region of 145 nucleotides occurring at the 3'-termini of the alfalfa mosaic virus (A1MV) RNAs, which contains the specific binding site f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…( Koper-Zwarthoff & Bol, 1980). While not identical the three sequences formed structures with three loops and in all of them the AUGC motif appears to be conserved.…”
Section: Short Communicationmentioning
confidence: 97%
“…( Koper-Zwarthoff & Bol, 1980). While not identical the three sequences formed structures with three loops and in all of them the AUGC motif appears to be conserved.…”
Section: Short Communicationmentioning
confidence: 97%
“…Conversely, AMV and ilarviruses lack a canonical CCA 3Ј end common to the TLS and further require the presence of their own viral CP to initiate replication (6). It has been shown that CP binds specifically to the 3Ј untranslated region found on all three AMV genomic RNAs as well as the subgenomic RNA4 (5,22,24). Genomic RNA1 and -2 encode proteins with replicase functions (33).…”
mentioning
confidence: 99%
“…CP binds specifically to the 3´ untranslated regions (3´UTRs) found on all four RNAs of the segmented AMV genome (5). The 180-nucleotide 3´UTR secondary structure likely consists of six hairpins, most of which are separated by single-stranded tetranucleotide AUGC repeats (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The 180-nucleotide 3´UTR secondary structure likely consists of six hairpins, most of which are separated by single-stranded tetranucleotide AUGC repeats (5)(6)(7)(8). These repeats are characteristic of AMV and ilarvirus RNA sequences and are important for CP binding (8)(9)(10)(11).…”
mentioning
confidence: 99%